(untitled) (Praxis Educativa, 2023)
In this article we propose a theoretical-methodological reflection on a research work that takes the form of an artistic (co)production workshop in a public secondary school located in a context of urban poverty in the Metropolitan Region of Buenos Aires (MRBA). We recovered field material produced during 2022 to explore the possibilities of this methodology. Working with artistic practices allows the unfolding of a narrative, a saying, at the same time that it is proposed as a training experience for students, connecting with the task that the school carries out on a daily basis.